Putusan Bebas Tindak Pidana Korupsi: Studi Putusan Pengadilan Negeri Ambon Nomor 12: PID.SUS-TPK/2024/PN.AMB - Salsabilla, Ditha Arizki; Sopacua, Margie Gladies; Taufik, Iqbal (MATAKAO Corruption Law Review, 2025)
An acquittal (vrijspraak), acquittal, if the defendant's guilt for the act charged to him is not proven legally and convincingly based on the results of the examination in court. Article 183 of the Criminal Procedure Code, A judge may not sentence someone unless he is convinced, with at least two valid pieces of evidence, that the crime actually occurred and the defendant is guilty of committing it. The research method used is the normative legal research type, which is carried out by examining library materials or secondary data, namely examining theories, concepts, legal principles and laws and regulations that are relevant to the problem being studied. The results of the study indicate that the application of material criminal law to corruption cases in the Ambon District Court decision case Number: 12 / Pid.Sus-TPK / 2024 / PN Amb.) was carried out in accordance with the legal facts, both statements from witnesses, statements from the defendant, and evidence. The form of the indictment made by the public prosecutor is appropriate because if the public prosecutor chooses to compile an indictment in the form of a subsidiary, then the systematic arrangement is where the crime threatened with the heaviest principal penalty is placed in the first layer or placed on the primary indictment and the crime threatened with a lighter penalty is placed on the indictment but in terms of proof it can cause difficulties because the proof of the primary indictment can touch the proof of the subsidiary indictment. The Judge's Legal Considerations in handing down the Acquittal was handed down to the Ambon District Court decision Number: 12 / Pid.Sus-TPK / 2024 / PN Amb.) because it was not legally and convincingly proven that the defendant was guilty of committing the corruption crime charged.